Essays on the economics of natural disasters - Hu, Yuchen, author; Cutler, Harvey, advisor; Zahran, Sammy, committee member; Mushinski, David, committee member; van de Lindt, John, committee member (Colorado State University. Libraries, 2020)
Natural hazards occur frequently, and the costs associated with these events are well into the billions of dollars. The rising frequency and costs from natural disasters require a comprehensive understanding of its impacts on the economic system and mitigation strategies for local communities that can minimize these losses. The purpose of Chapter 1 is to demonstrate a linkage between civil engineering and economic models to accomplish these objectives. To do this, I build a spatial computable general equilibrium model (SCGE) for Shelby County in Tennessee that requires an extensive data set dependent upon eight different data sources. I then develop advanced methods that integrate simulation models from engineering and economics. Civil engineers have created a range of simulation models that estimates the impact of a hypothetical earthquake on damages to buildings, utilities, and transportation network. These damages are integrated into the SCGE model to simulate a range of economic outcomes. I find that the SCGE model is more advanced in capturing the adjustment behaviors of businesses and households to external shocks compared to previous attempts. I also find that to better estimate the economic impacts, we need to simulate the model with the three types of physical damages jointly and not individually. Chapter 2 investigates a hidden layer of the impact of natural disasters, which is the spillover effect due to disaster-induced migration on the receiving areas' labor markets. Using the difference in difference approach, I empirically compare the hourly wage rates in areas that received the evacuees from Hurricane Katrina to areas that didn't. I find that in the export-oriented industry, the inflow of migrants due to Katrina slightly reduces the hourly wage rates for both the low and the high-skilled workers. However, in the localized industries where the inflow of the migrants also increased the demand for local goods and services, the inflow of evacuees raises the hourly wage rates the high-skilled workers and imposes no significant impacts for the low-skilled workers. These results are consistent with previous literature in that immigrants did impact the local labor markets but at a small magnitude. Chapter 3 proposes the setup of a Rainy-Day Fund (RDF) through tax increase/hikes for local governments in preparing for external shocks in the future. To minimize the costs of tax hikes to the economy and achieve the target amount of RDF, I use the SCGE model developed in Chapter 1 to solve for an optimal path of tax hikes over time. The process starts with an endogenized cost function measured by the foregone output that could be produced had there been no changes in the tax system. Built on the profit and utility maximization in response to changes in taxes, the cost function expands the theoretical setup of Barro (1979) and Ghosh (1995) by allowing any factors that influence the output to enter the optimization process. Moreover, the cost function in any period depends on not only the tax rates in that period but also the tax rates in previous periods, since any changes to the tax rates previously can influence the current economy through changes in investment and capital. I find that the optimal trajectory of the tax hikes tends to be rising in time. The rate of the increase depends on the magnitude of labor supply elasticity to real wages, and the interest of the regional planners to include economic outcomes beyond the planning horizon.
Keywords: labor market; natural disaster; migration; CGE